Noise and vibration prediction on a hard disk drive using statistical energy analysis with the incorporation of finite element and experimental methods - Chiang, Lilian Chang Wee. (2008)
Statistical Energy Analysis (SEA) is used together with Finite Element Method (FEM) and test-based measurements for the prediction of wide-bandwidth noise and vibration. The vibroacoustics behaviour predictions of complex small structures, namely the hard disk drive had been investigated. Noise and vibration predictions on small complex structures are difficult because of the involvement of high frequencies, numerous structural parts and random broadband vibration.